Basic fibroblast growth factor signalling regulates cancer stem cells in lung cancer A549 cells. (8th July 2019) - Meng, Yousheng; Bai, Xiaoyan; Huang, Yuandong; He, Lang; Zhang, Zhengwei; Li, Xia; Cui, Dandan; Yang, Xuemei
Abstract: Objectives: The basic fibroblast growth factor (bFGF)/fibroblast growth factor receptor (FGFR) signal transductional pathway plays an important role not only in tumour, but also in tumour stem cells. Thus, this study was designed to investigate the effects of bFGF signalling on cancer stem cells of lung cancer. Methods: We blocked bFGF/FGFR signalling in cisplatin (DDP) selected A549 by knocking down bFGF via RNA interference, and subsequently, the stem cell marker of OCT-4 was determined, and cell proliferation, clone formation, invasiveness, apoptosis and drug resistance abilities of DDP selected A549 cells were investigated. Key findings: The expressions of bFGF and OCT-4 in DDP selected A549 were higher than that of A549 cells. The findings suggested blocking of bFGF/FGFR signalling resulted in downregulation of bFGF, reduction in cell proliferation, clone formation, invasion and drug resistance abilities, and increase in cell apoptosis. Furthermore, our results also revealed OCT-4 was reduced after bFGF signalling blocking. Conclusions: In conclusion, our study suggested that bFGF/FGFR signalling plays an important role in maintaining lung cancer stem cell characteristics and regulating expression of cancer stem cell marker of OCT-4.